Śaivism through the ages - Siddhantashastree, Rabindra Kumar, 1918- (Munshiram Manoharlal Publishers, 1974)
Presentation of the thesis that Siva is an Aryan god and Saivism is a contribution of the Aryans to Indic philosophy.